지역 소멸 위기에 대응한 공유가치창출형 지역재생 - 이승철; Sung-cheol Lee; 우정석; Jungsuk Woo (한국경제지리학회지, 2024)
도시재생은 지역 소멸 문제를 해결하기 위한 접근 방법의 하나로 낙후된 도시 공간의 물리적 개선 및 지역 내 일자리 창출을 통한 지역발전의 선순환 고리를 형성하는 사업이다. 쇠퇴지역의 재생사업을 성공시키기 위한 기본 전제 조건은 공공성과 수익성 기반의 지속 가능성이라 할 수 있다. 그러나 지금까지 정부가 도시재생사업을 통해 쇠퇴 및 낙후지역의 활성화를 강력하게 추진했음에도 불구하고 이에 대한 실질적인 성과가 낮은 원인은 도시재생의 공공성과 수익성, 그리고 지속 가능성을 충분히 고려하지 않았기 때문이다. 이에 본 연구는 우리나라 도시재생 방식의 한계에 대한 대안으로 공유가치창출(Creating Shared Value: CSV) 기반의 지역재생을 제시하고 개념화하고자 한다. CSV 기반 지역재생은 지역사회에서 영리 기업과 지역이 공유가치를 창출하면서 지속 가능한 발전모델을 만드는 것이다. 이는 지역 이익 기반의 도시재생을 위해 지역에 이해관계를 둔 기업의 참여와 지역기업-지역의 전략적 조응으로 지역과 기업이 공유하는 가치를 도출하여 상생할 수 있는 공공성과 수익성에 기반을 둔 지속 가능한 도시재생 전략을 제시해준다. 특히 CSV 기반 지역재생은 지역 소멸위기에 대응하여 자생성이 떨어진 지역의 물리적 환경개선을 넘어 지역성에 기초한 가치를 발굴하고 사회-경제적 자생능력을 키워주는 역할을 할 것으로 기대한다. Local regeneration is an approach to address the issues of regional extinction by improving deteriorated local spaces and creating local employment opportunities, thereby forming virtuous cycle of local and regional development. The fundamental prerequisites for the successful implementation of local regeneration project in declining region are sustainability based on both publicity and profitability. Nevertheless, despite the government’s significant efforts to revitalize declining regions through local regeneration projects, the tangible outcomes have been limited. This lack of success can be attributed to insufficient consideration of the publicity, profitability and sustainability within local regeneration project. To address these limitations, this study aims to propose and conceptualize an alternative approach to local regeneration based on Creating Shared Value(CSV), which can enhance the sustainability and effectiveness of such projects in South Korea. CSV-oriented local regeneration involves creating shared value between profit-driven local firms and local communities, fostering a sustainable development model. By strategic coupling between local firms and local communities, it seeks to generate shared value that enables both communities and businesses to thrive within the local area. Rooted in the principles of publicity and profitability, this CSV-oriented local regeneration offers a sustainable local regeneration strategy. Notably, it responds to the challenges of regional extinction crisis by not only improving physical environment of declining areas but also uncovering value rooted in local and regional identity and enhancing community’s socio-economic capacity for self-reliance.